2014
DOI: 10.1055/s-0034-1382949
|View full text |Cite
|
Sign up to set email alerts
|

Kavalactones, A Novel Class of Protein Glycation and Lipid Peroxidation Inhibitors

Abstract: Both advanced glycation endproducts and advanced lipoxidation endproducts are implicated in many age-related chronic diseases and in protein ageing. In this study, kawain, methysticin, and dihydromethysticin, all belonging to the group of kavalactones, were identified as advanced glycation endproduct inhibitors. With IC50 values of 43.5 ± 1.2 µM and 45.0 ± 1.3 µM for kawain and methysticin, respectively, the compounds inhibited the in vitro protein glycation significantly better than aminoguanidine (IC50 = 231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It is well-known that no specific examination test is available to check or reveal the attack or adverse effects of any phytomedicines; 29 however, a recent accurate history and use of proper histopathology tests may help control or handle such kind of situations. 30,31 Even in most of the situations, no apparent symptoms are available, and no physical signs can be followed; however, IgG, anti-HBs as well as anti-HIV tests are the possible solution to detect such AV toxicity. Although supportive medication is used widely, in most of the cases, discontinuation of the herb also leads to patient recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that no specific examination test is available to check or reveal the attack or adverse effects of any phytomedicines; 29 however, a recent accurate history and use of proper histopathology tests may help control or handle such kind of situations. 30,31 Even in most of the situations, no apparent symptoms are available, and no physical signs can be followed; however, IgG, anti-HBs as well as anti-HIV tests are the possible solution to detect such AV toxicity. Although supportive medication is used widely, in most of the cases, discontinuation of the herb also leads to patient recovery.…”
Section: Discussionmentioning
confidence: 99%
“…With IC50 values of 43.5 ± 1.2 μM and 45.0 ± 1.3 μM for 7 and 8, respectively, and the kavalactones inhibited the in vitro protein glycation significantly better than aminoguanidine (IC50 = 231.0 ± 11.5 μM; p = 0.01), an established reference compound. [36] Hepatotoxicity With case reports of kava hepatotoxicity, hepatotoxicity of main constituents of kava, kavalactones, were evaluated. Hepatotoxicity of compounds 7, 8 and 14 on human hepatocytes (HepG2) was assessed using lactate dehydrogenase (LDH) and ethidium bromidemide assays by Zou et al They concluded that compound 3 had minimal cytotoxicity, compound 8 had moderate concentration-dependent toxicity, and compound 14 showed obvious toxicity with about 40% reduction in viability in the EB assay.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…3,5 A plethora of plants is available where they are actively used to treat disorders such as respiratory, central nervous, and cardiovascular system diseases. [6][7][8] Ephedra sinica (ES) is also considered as one of the most significant plants in traditional medicine. It belongs to the family Ephedraceae and known with its synonym in Korea, China, and Japan, i.e., Ma-huang.…”
Section: Introductionmentioning
confidence: 99%